1994
DOI: 10.1111/j.1464-5491.1994.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Smoking and Albuminuria in Children with Insulin‐dependent Diabetes

Abstract: Recent evidence suggests the rise in urinary albumin excretion preceding diabetic nephropathy may represent a continuum. We therefore studied factors relating to albumin excretion rate in children with insulin-dependent diabetes. Normal overnight albumin excretion rate was determined in 690 healthy schoolchildren. The 95th centile was 7.2 micrograms min-1. Patients included 169 children with IDDM aged 12.4 +/- 3.1 years who performed 4.8 +/- 0.4 overnight collections during 15 +/- 0.5 months and were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 8 publications
6
38
0
1
Order By: Relevance
“…Using these criteria, we showed that hypertension almost doubled the risk of developing ESRF, corroborating the hypothesis of early systemic and renal hemodynamic abnormalities in the genesis of DN (46). Smoking has been associated with microalbuminuria in IDDM (47,48), but it is not clear if it represents an independent factor contributing to the progression of renal disease (49). The thromboxane-induced vasoconstriction effect of smoking on temporary elevation of blood pressure (50) associated with the observation of insulin resistance among smokers (51) raises the possibility that smoking predisposes to a persistent blood pressure increase and consequently to renal damage.…”
Section: Discussionsupporting
confidence: 81%
“…Using these criteria, we showed that hypertension almost doubled the risk of developing ESRF, corroborating the hypothesis of early systemic and renal hemodynamic abnormalities in the genesis of DN (46). Smoking has been associated with microalbuminuria in IDDM (47,48), but it is not clear if it represents an independent factor contributing to the progression of renal disease (49). The thromboxane-induced vasoconstriction effect of smoking on temporary elevation of blood pressure (50) associated with the observation of insulin resistance among smokers (51) raises the possibility that smoking predisposes to a persistent blood pressure increase and consequently to renal damage.…”
Section: Discussionsupporting
confidence: 81%
“…To obtain valid determination of the rate of decline in GFR, the following requirements should be fulfilled: the applied GFR method should have good accuracy and precision, repeated measurements of GFR should be performed (approximately every 6 -12 months), and the observation period should be extended to at least 2 years (25). These requirements have been fulfilled in our study, in which the follow-up time was 7 years (range [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…RESEARCH DESIGN AND METHODS -We identified all albuminuric type 1 diabetic patients (n ϭ 301) followed for at least 3 years, median (range) 7 years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), who underwent at least yearly measurement of glomerular filtration rate (GFR) by the 51 Cr-EDTA plasma clearance technique (n ϭ 8, range 3-24). In total, 192 men and 109 women were included (age [mean Ϯ SD] 36 Ϯ 11 years, duration of diabetes 22 Ϯ 8 years); 271 patients were treated with antihypertensive drugs, predominantly ACE inhibitors in 179 patients.…”
mentioning
confidence: 99%
“…The importance of achieving glycemic goals should be reviewed and reinforced. As part of general education on cardiovascular health, counseling should be given for smoking cessation, or encouragement given to not begin the use of tobacco products, since smoking increases microvascular complications, including hypertension (131,144). There is good evidence that ACE inhibitor treatment of hypertension decreases the rate of decline of renal function in adults (134,135).…”
Section: Definition Of Hypertensionmentioning
confidence: 99%